Studies on Liver Factors which Exert an Inhibitory Effect on Platelet Aggregation - Rogowski, W; GaŁasiński, W; Bańkowski, E; Rzeczycki, W (Thrombosis and Haemostasis, 1971)
The inactivating effect of rabbit liver homogenates on platelet aggregation was investigated.The active substances were found in a nonprotein fraction of the liver homogenates. They were separated and identified as nucleotides and nucleosides. It was found that the platelet aggregation inhibiting substances obtained from the liver, inactivated the platelet aggregating factors, such as ADP, thrombin and collagen. Nucleosides and nucleotides were chromatographically separated from the liver homogenates, and their effect examined on the platelet aggregating factors. The probable mechanism of their inactivation and their pathophysiological significance are discussed.